PERAN TPQ DALAM PEMBENTUKAN KARAKTER PADA ANAK USIA DINI BERBASIS PENDIDIKAN AGAMA ISLAM - Sangadah, Wasilatus; Basiran, Basiran (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
In moral education in children can not be separated from the role of Education, both in formal and non-formal education. TPQ (Taman Pendidikan Al-Quran) is one of the means of non-formal education for children to assist in understanding and practicing the teachings of islam, with the material in which there is worship Amali'ah and worship qauli'ah as well as aqidah, morals, al-Qur'an and pasholatan. TPQ as a non-formal institution that has a role, certainly requires qualified human resources. TPQ as a non-formal educational institution has an important role in the world of education, besides that there are still many parents who have not been able to educate independently thus understanding time, science, and teaching methods. Thus, TPQ is expected to improve performance in developing the potential of children in the development of knowledge, morals, and skills in the field of religion by using an approach that is in accordance with the Qur'an and Hadith. TPQ Ar-rohman is one of the TPQ used by the people of Borobudur village, Borobudur District, Magelang regency. This study uses descriptive research with descriptive quantitative design. Data collection technique is done by direct observation to the target TPQ and interviews of several research subject